Multiple prosthetic vascular implants into the acutely ischaemic myocardium - Clarke, D. B. (1970)
In nine dogs submitted to a severe myocardial ischaemic challenge, multiple prosthetic implants running from the descending aorta to myocardial tunnels were successful in sustaining effective ventricular contraction for a mean period of 27 minutes. A control series of five dogs and five animals, in which the prostheses clotted, developed ventricular fibrillation within six minutes of the ligation of either the left or both coronary arteries. It is suggested that these findings, although not applicable to clinical practice, should stimulate further investigation into the surgical support of the acutely ischaemic myocardium.